A Qualitative Exploration of the Referral Process of Children with Common Infections from Private Low-Level Health Facilities in Western Uganda - Mwanga-Amumpaire, Juliet; Kalyango, Joan Nakayaga; Ndeezi, Grace; Rujumba, Joseph; Owokuhaisa, Judith; Lundborg, Cecilia Stålsby; Alfvén, Tobias; Obua, Celestino; Källander, Karin (Children, 2021)
Over 50% of sick children are treated by private primary-level facilities, but data on patient referral processes from such facilities are limited. We explored the perspectives of healthcare providers and child caretakers on the referral process of children with common childhood infections from private low-level health facilities in Mbarara District. We carried out 43 in-depth interviews with health workers and caretakers of sick children, purposively selected from 30 facilities, until data saturation was achieved. The issues discussed included the process of referral, challenges in referral completion and ways to improve the process. We used thematic analysis, using a combined Deductive /inductive approach. The reasons for where and how to refer were shaped by the patients’ clinical characteristics, the caretakers’ ability to pay and health workers’ perceptions. Caretaker non-adherence to referral and inadequate communication between health facilities were the major challenges to the referral process. Suggestions for improving referrals were hinged on procedures to promote caretaker adherence to referral, including reducing waiting time and minimising the expenses incurred by caretakers. We recommend that triage at referral facilities should be improved and that health workers in low-level private health facilities (LLPHFs) should routinely be included in the capacity-building trainings organized by the Ministry of Health (MoH) and in workshops to disseminate health policies and national healthcare guidelines. Further research should be done on the effect of improving communication between LLPHFs and referral health facilities by affordable means, such as telephone, and the impact of community initiatives, such as transport vouchers, on promoting adherence to referral for sick children.
Keywords: Referral; Primary private health facilities; Low-income countries